2021
DOI: 10.1080/10494820.2021.1979047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an academic satisfaction model in E-learning education contexts

Abstract: The urgent imperative to "move online", caused by the recent Covid-19 pandemic, has led to an in-depth study of the psychological factors involved in designing successful online learning experiences. The socialcognitive model of academic satisfaction has been widely researched in conventional educational contexts in different countries. The purpose of this research was to evaluate the adequacy of this model in e-learning education contexts. The method used was path analysis, including as independent variables:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…These results largely corroborated earlier studies that has showed positive relations of goal progress, environmental support and self‐efficacy to AS 2,36–38 . Goal progress (i.e.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results largely corroborated earlier studies that has showed positive relations of goal progress, environmental support and self‐efficacy to AS 2,36–38 . Goal progress (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…These results largely corroborated earlier studies that has showed positive relations of goal progress, environmental support and selfefficacy to AS. 2,[36][37][38] Goal progress (i.e. the perception that one is making progress at personally valued goals) was shown to be a particularly reliable predictor of domain satisfaction 13 ; environment and resources are relevant to AS because they can support and facilitate medical students' goal-directed involvement; self-efficacy is another core construct that there is substantial evidence supporting its predictive validity in medical education literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the validation process by the students, lecturers and experts had been completed, the teaching model was revised based on the corrections and suggestions from the experts. This stage was important in order to ensure a quality final product of the development research (Zalazar et al, 2021). Revisions made by the researchers relate to changes in teaching models that were not in accordance with the needs of the students and lecturers, spelling errors, structures that are not in accordance with the applicable curriculum, and suggestions to use more familiar platforms in teaching online.…”
Section: Revising Product Development Resultsmentioning
confidence: 99%